2021
DOI: 10.1093/jhps/hnab057
|View full text |Cite
|
Sign up to set email alerts
|

The role of iliocapsularis in hip pathology: a scoping review

Abstract: The iliocapsularis is a relatively unheard-of muscle, located deep in the hip covering the anteromedial capsule of the hip joint. Little is known about this constant muscle despite its clinical relevance. The aims of this scoping review are to collate the various research studies reporting on the detailed anatomy and function of iliocapsularis and to demonstrate how inter-individual differences in iliocapsularis can be used as a clinical adjunct in guiding diagnosis and treatment of certain hip joint pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…An intact ligamentum teres was also found to be a predictor of a relatively low risk of instability [20]. The hypertrophy of extracapsular iliocapsular muscle was considered to be a secondary sign of hip dysplasia [33]. However, very few studies have focused on the morphological features of the capsule, which prompted us to undertake this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intact ligamentum teres was also found to be a predictor of a relatively low risk of instability [20]. The hypertrophy of extracapsular iliocapsular muscle was considered to be a secondary sign of hip dysplasia [33]. However, very few studies have focused on the morphological features of the capsule, which prompted us to undertake this study.…”
Section: Discussionmentioning
confidence: 99%
“…[24]. The previous investigation on the morphology of soft tissue around the hip joint only revealed that hypertrophy of labrum and iliocapsularis muscle could be related to hip instability [29, 33]. However, knowledge gaps exist about the relationship between the capsular morphology and the instability of the hip joint.…”
Section: Introductionmentioning
confidence: 99%
“…These exclusions resulted in 28 PRL articles which included the ICm. Of the 28 publications mentioning the ICm, 19 highlighted the morphology and proposed functional roles of the muscle (Babst et al, 2011;Baker et al, 2022;Das & Singh, 1950;Elvan et al, 2019;Haefeli et al, 2015;Hammoud et al, 2014;Keet et al, 2021;Konno et al, 2021;Lawrenson et al, 2017Lawrenson et al, , 2019Lawrenson et al, , 2020Philippon et al, 2014;Pourcho et al, 2015;Retchford et al, 2013;Ricci & Özçakar, 2019;Saito et al, 2021;Walters et al, 2014;Wang et al, 2021;Ward et al, 2000). Nine additional studies reported the presence of the ICm using clinical scenarios consisting of surgical interventions and diagnostic imaging (Agten et al, 2016;Camenzind et al, 2018;Fagotti et al, 2020;Harris, 2016;Kalhor et al, 2021;Siebenrock et al, 2015;Spiker et al, 2021;Wyatt et al, 2017;Xu et al, 2021).…”
Section: Primary Literature Searchmentioning
confidence: 99%